Beyond descriptive statistics: using additional analyses to determine the technological feasibility of meeting a new exposure limit. Issue 9 (27th August 2021) - Roberts, Benjamin; Tarpey, Taylor; Zoghby, Nicole; Slavin, Thomas
Abstract: In determining whether a new permissible exposure limit is technologically feasible, the Occupational Safety and Health Administration (OSHA) and various courts have used poorly defined criteria such as whether "most employers most of the time" are able to comply with a standard. This vague definition creates problems when employers try to determine the best way to protect their workers and estimate the costs to remain in compliance with the permissible exposure limit. This article proposes a more rigorous approach to determine feasibility. By utilizing the best available statistical methods, employers and rule makers can better understand the variability within existing exposure data to determine the feasibility of new exposure limits. There are several readily available statistical tools that can be used for this purpose. To illustrate these techniques, a subset of data from the foundry industry and analysis from the OSHA respirable crystalline silica rulemaking proceeding are compared to methods published by the National Institute for Occupational Safety and Health in 1977 and a more sophisticated Bayesian approach. The results of this analysis suggest that complying with a new permissible exposure limit is more challenging than what is implied by OSHA's analysis, and calls into question its method of determining compliance. In the same vein, OSHA should move away from assessing compliance based on individual measurements and instead use a statistical approach to determine if a workplace is in compliance. These changes will encourage employers to better characterize occupational exposures, and will ultimately lead to better protection for employees while also providing employers protection from violations due to one-off overexposures.